RECENT ADVANCES OF CAST-IN-SITU PILE INTEGRITY TEST IN INDONESIA - Aksan Kawanda (Universitas Trisakti, 2018)
Deep foundations, especially cast-in-situ piles became popular and key support for most structures in limited land, so as Jakarta. The piles quality became highly dependent on the soil condition and the skill of the contactors. It’s underneath the ground and this makes inspection to its quality became much more difficult. There is many methods for inspection, either by destructive method, i.e. coring, to non-destructive method like low strain integrity test (PIT), cross-hole sonic logging (CSL) and latest is thermal integrity profiler (TIP). Some advances in applicating and evaluating the pile integrity discussed here as well as its advantages and limitations.